SYSTEMATIC LITERATURE REVIEW: THE EFFECTIVENESS OF CANVA AND WORDWALL-ASSISTED DISCOVERY LEARNING ON STUDENTS' MATHEMATICAL CONNECTION SKILLS AND LEARNING INTERESTS - Firda Anisa Sal Sabila; Iyam Maryati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Mathematical connection skills and learning interest are two important aspects in mathematics learning that influence student learning success. Low mathematical connection skills cause students to experience difficulties in connecting mathematical concepts and relating them to everyday life. In addition, low learning interest impacts a lack of student engagement during the learning process. This study aims to analyze the effectiveness of the implementation of Discovery Learning assisted by Canva and Wordwall on students' mathematical connection skills and learning interest through a Systematic Literature Review (SLR) approach. The articles analyzed were obtained through Google Scholar and accredited national journals using the 2019–2024 period. The article selection process used the PRISMA stages which include identification, screening, eligibility, and inclusion. A total of 20 articles that met the inclusion criteria were systematically analyzed. The results of the study indicate that Discovery Learning is effective in improving mathematical connection skills through the processes of exploration, information processing, verification, and generalization of concepts. Canva plays a role in facilitating the visualization of mathematical concepts in an interesting and systematic manner, thereby helping students' conceptual understanding. Meanwhile, Wordwall functions as an interactive practice medium that increases students' active participation, motivation, and learning interest. The integration of Discovery Learning, Canva, and Wordwall creates constructive, interactive, and meaningful mathematics learning, thereby improving the quality of learning both cognitively and affectively.